Measurement of the γγ∗→η and γγ∗→η′ transition form factors - Amo Sanchez, Pablo del; Marks, Jörg; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2011)
We study the reactions e+e−→e+e−η(') in the single-tag mode and measure the γγ∗→η(') transition form factors in the momentum-transfer range from 4 to 40 GeV2. The analysis is based on 469 fb−1 of integrated luminosity collected at PEP-II with the BABAR detector at e+e− center-of-mass energies near 10.6 GeV.
Gesehen am 04.10.2022